Comparative Structural Biology of Eubacterial and Archaeal Oligosaccharyltransferases - Maita, Nobuo (American Society for Biochemistry and Molecular Biology, 2010)
Oligosaccharyltransferase (OST) catalyzes the transfer of an oligosaccharide from a lipid donor to an asparagine residue in nascent polypeptide chains. In the bacterium Campylobacter jejuni, a single-subunit membrane protein, PglB, catalyzes N-glycosylation. We report the 2.8 Å resolution crystal structure of the C-terminal globular domain of PglB and its comparison with the previously determined structure from the archaeon Pyrococcus AglB. The two distantly related oligosaccharyltransferases share unexpected structural similarity beyond that expected from the sequence comparison. The common architecture of the putative catalytic sites revealed a new catalytic motif in PglB. Site-directed mutagenesis analyses confirmed the contribution of this motif to the catalytic function. Bacterial PglB and archaeal AglB constitute a protein family of the catalytic subunit of OST along with STT3 from eukaryotes. A structure-aided multiple sequence alignment of the STT3/PglB/AglB protein family revealed three types of OST catalytic centers. This novel classification will provide a useful framework for understanding the enzymatic properties of the OST enzymes from Eukarya, Archaea, and Bacteria.